Mesenchymal Stem Cells (MSCs): A Novel Therapy for Type 2 Diabetes - Shuang Gao; Yuanyuan Zhang; Kaini Liang; Ran Bi; Yanan Du (Stem Cells International)
Although plenty of drugs are currently available for type 2 diabetes mellitus (T2DM), a subset of patients still failed to restore normoglycemia. Recent studies proved that symptoms of T2DM patients who are unresponsive to conventional medications could be relieved with mesenchymal stem/stromal cell (MSC) therapy. However, the lack of systematic summary and analysis for animal and clinical studies of T2DM has limited the establishment of standard guidelines in anti-T2DM MSC therapy. Besides, the therapeutic mechanisms of MSCs to combat T2DM have not been thoroughly understood. In this review, we present an overview of the current status of MSC therapy in treating T2DM for both animal studies and clinical studies. Potential mechanisms of MSC-based intervention on multiple pathological processes of T2DM, such as β-cell exhaustion, hepatic dysfunction, insulin resistance, and systemic inflammation, are also delineated. Moreover, we highlight the importance of understanding the pharmacokinetics (PK) of transplanted cells and discuss the hurdles in MSC-based T2DM therapy toward future clinical applications.